Location of MMPs in human radicular dentin and the effects of MMPs inhibitor on the bonding stability of fiber posts to radicular dentin. (May 2022) - Yu, H.H.; Liu, J.; Liao, Z.X.; Yu, F.; Qiu, B.Y.; Zhou, M.D.; Li, F.; Chen, J.H.; Zhou, W.; Zhang, L.
Abstract: This study explored the location of MMP-2, -3, -8 in human root dentin and the inhibition of EGCG/EGCG-3Me on dentin-originated collagen proteases activities. Also, the study evaluated EGCG/EGCG-3Me modified etch-and-rinse adhesives (Single Bond 2, SB 2) for their bonding stabilities to intraradicular dentin. Immunostaining and liquid chip analysis demonstrated that MMP-2 and MMP-8 are widely distributed in root dentin while MMP-3 shows a higher fluorescence intensity in the middle and apical third of the root. The contents of MMP-2, -3 and -8 varies in different locations of human tooth root and MMP-2 has the highest content than MMP-3 and MMP-8 at each third of teeth root. Both EGCG and EGCG-3Me showed an inhibitory effect on the root dentin-derived MMPs in a concentration dependent manner (P < 0.05) and the inhibitory activity of EGCG-3ME was stronger than that of EGCG at the same concentration (P < 0.05). EGCG and EGCG-3Me were incorporated separately into the adhesive SB 2 at concentrations of 200, and 400 μg/mL respectively. The immediate push-out strength of SB 2 was not compromised by EGCG/EGCG-3Me modification. EGCG/EGCG-3Me modified adhesive had higher push-out strength than SB 2 after thermocycling, showing no correlation with concentration.